2020
DOI: 10.1111/1460-6984.12537
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aphasia on communication in couples

Abstract: BackgroundCommunication is at the heart of relationships, especially for couples. When language is altered, as it is in aphasia, communication in couples can be affected.AimsTo explore how members of a couple perceive the impact of aphasia on their communication.Methods & ProceduresNine French‐speaking couples participated in the study. One member of each couple had chronic stroke‐related aphasia, which varied in type and severity. The 18 participants took part in individual semi‐structured interviews to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…For instance, in dementia, relationship functioning seems to be strongly related to behavioral problems of the patient (Quinn et al, 2009). However, except for one study that focused on stroke-related aphasia and its impact on couples' communication (Croteau et al, 2020) and two studies suggesting that personality changes in TBI patients might have contributed to emotional distance between the partners (Bodley-Scott and Riley, 2015;O'Keeffe et al, 2020), no studies showed indications that cognitive impairments were responsible for the relationship challenges summarized in this review. Second, the current review focused on dyadic processes and their relation to dyadic outcomes.…”
Section: Strengths and Limitationsmentioning
confidence: 89%
See 3 more Smart Citations
“…For instance, in dementia, relationship functioning seems to be strongly related to behavioral problems of the patient (Quinn et al, 2009). However, except for one study that focused on stroke-related aphasia and its impact on couples' communication (Croteau et al, 2020) and two studies suggesting that personality changes in TBI patients might have contributed to emotional distance between the partners (Bodley-Scott and Riley, 2015;O'Keeffe et al, 2020), no studies showed indications that cognitive impairments were responsible for the relationship challenges summarized in this review. Second, the current review focused on dyadic processes and their relation to dyadic outcomes.…”
Section: Strengths and Limitationsmentioning
confidence: 89%
“…Some studies came to the overall conclusion that couples did not adjust well to physical or sensory disability, as is evidenced, for example, by the theme of "the alienated couple" reported by Wawrziczny et al (2019) in MS couples. Other examples include permanently altered communication in couples coping with stroke (Croteau et al, 2020), or the finding that the majority of spouses of TBI patients felt their love had changed toward a caring relationship lacking romantic aspects (Bodley-Scott and Riley, 2015). Other qualitative studies in this review, however, presented a more balanced account.…”
Section: Dyadic Adjustmentmentioning
confidence: 94%
See 2 more Smart Citations
“…Common age can be considered an important factor in recovery: some studies suggest that recovery from stroke aphasia has failed in patients over seventy years of age compared to younger patients; however, at any age, various degrees of recovery can occur even in remote times from brain injury. [5,6].…”
Section: Contents Of the Manuscriptmentioning
confidence: 99%